PROFESIONALISME PENGAWAS PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN KEMENTERIAN AGAMA KABUPATEN PAMEKASAN - Saiful Arif (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
This research based article is describing the professionalism of Islamic Education Supervisors in Pamekasan Religious Department.  There are six focuses of this research, they are 1) how is the professionalism degree of the Religious Department Education Supervisor?, 2) what is the level of professionalism of the education Supervisor in the standart competence of managerial supervision of Pamekasan Religious Department?, 3) how is the professionalism of education supervisor in the standart competence of academic supervision in Pamekasan Religious Department, 4) how is the professionalism of education supervisor in the standart competence of education evaluation in Pamekasan Religious Department, 5) how is the professionalism of education supervisor in the standart competence of developmental research in Pamekasan Religious Department, 6) how is the professionalism of education supervisor in the social standart competence in Pamekasan Religious Department.